MENEGUHKAN NILAI ASWAJA DALAM BINGKAI PENDIDIKAN ISLAM ANTI RADIKALISME - Uswatun Khasanah (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to reveal how to confirm the value of Aswaja in Islamic education as an effort to prevent radicalism at Pondok Pesantren PDF Walindo Siti Zaenab Manba’ul Falah KPBR IV Berbaur Kabupaten Pekalongan. This qualitative research used purposive sampling technique in determining the informants, namely caregivers and teachers. The data were analyzed with qualitative descriptive techniques including data collection, reduction and presentation. The studyshowed that in principle PP.PDF Walindo rejects Islamic radicalism because it is contrary to the Aswaja principle. The Aswaja principles, namely tawasuth, ta'adul, tawazun and tasamuh, are believed to be used as anti-radicalism values that can be internalized in the educational process so that they can protect students from Islamic radicalism which is now increasingly spreading massively. The preventive actions taken include accepting students and teachers who have a moderate understanding and have an Aswaja ideological background. Anti-radicalism Islamic education is implemented through a modeling strategy, planting Aswaja values, civic education, and habituation of the Aswaja tradition.